When too much punishment decreases legality. The case of coca-reducing policies in Colombia - Juanita Vasquez Escallon (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
States want their people to follow the law. They can either persuade them, sanction law-breakers, or both. But sanctions do not only alter people s perception of risks and costs; they also affect how people view their state and its legitimacy, unleashing a series of non-economic factors that determine compliance with the law. In fact, when a sanction is perceived as unjust it may be inefficient in reducing law violations and could crowd-out legality in other aspects of life. Law scholars warn against violating the principle of proportionality by exerting extreme punishment in comparison with the magnitude of the crime, as it may result in the loss of citizen cooperation with the law. I take one of Colombia s drug-reducing policies, aerial spraying of coca crops and study the effect of its disproportionate use on legal crops. My results point to a non-linear effect of punishment on legality: spraying shocks or extreme spraying in relation to the amount of illegal crops found reduce engagement in legal crops, where as proportional levels of spraying induce legality. I use four different sources of data to test this relationship: macro data on all coca growing municipalities in Colombia, and micro data of three very different sets of farmers, namely coca growers surveyed by the UNODC, farmers that are beneficiaries of Colombia s biggest alternative development Program (Forest Warden Families) and coffee growers in municipalities that have had coca. I find the same results in all four samples and conclude that when the state overdoes its coercive actions, these can backfire and crowd out legality.
Keywords: D78; K42; Q12; 330